Current issues of regulating on recording of the employee’s labor activities - O. V. Chornous (Bulletin of Kharkiv National University of Internal Affairs)
This article has analyzed the current labor legislation on recording of an employee’s labor activity. The study focuses on the settlement of theoretical and practical problematic aspects of the process of employment records digitalization, and on the non-infringement of employees’ and pensioners’ labor rights and as subjects of labor relations in this regard.